The Relative Valuation of American Currency Spot and Futures Options: Theory and Empirical Tests - Ogden, Joseph P.; Tucker, Alan L. (Journal of Financial and Quantitative Analysis, 1988)
Joseph P. Ogden, Alan L. Tucker, The Relative Valuation of American Currency Spot and Futures Options: Theory and Empirical Tests, The Journal of Financial and Quantitative Analysis, Vol. 23, No. 4 (Dec., 1988), pp. 351-368